Stability of thermoelastic sliding problem with contact pressure-dependent thermal contact resistance. (1st November 2022) - Lee, Yongwoo; Jang, Yong Hoon
Abstract: The sliding contact problem of a rigid indenter over an elastic body with constant temperature difference was investigated using finite element method by considering a contact pressure-dependent thermal resistance. The stability boundary was identified by inspecting the transient contact behaviors, which showed a linear relationship between two nondimensional parameters at the log scale. This proportionality resulted in a nondimensional ratio, which depended on temperature, contact resistance, and sliding speed in the case of unit nondimensional material properties, suggesting "critical temperature difference". Moreover, the inclusion of Poisson ratio prevented the indefinite bifurcation behavior and led to a finite length scale in the steady state. Highlights: The thermoelastic sliding problem with a thermal contact resistance is numerically obtained. The linear stability boundary at the log scale is identified. The proportionality suggests a critical temperature difference. The Poisson ratio prevents the indefinite bifurcation behavior.